AB1000 Rheumathoid arthritis misdiagnosis and osteoarthritis as the most frequent cause for diagnosis mistake. (23rd January 2014) - Santos-Moreno, P.; Bello, J.M.; Cubides, M.; Amador, L.; Zambrano, D.; Villarreal, L.; Urbina, A.
Abstract : Background: There is a lack of expertise in the diagnosis of rheumatoid arthritis (RA) in primary care centers maybe worldwide and commonly, many patients with osteoarthritis (OA) are misdiagnosed with RA, leading to wrong treatment with consequent clinical impact. Objectives: The aim of this study was to describe demographic and clinical characteristics of a cohort of patients with OA derived to a specialized in RA center with presumptive RA diagnosis. Methods: A descriptive cross sectional study was realized. There were revised records of patients that were referred to a specialized in RA center in a 12 month period with presumptive diagnosis of this disease. For confirmation or ruling-out RA diagnosis was followed a standardized protocol: a complete medical record was fulfilled by a rheumatologist; it was measured rheumatoid factor and anti-citrullinated antibodies, and finally other laboratories depending on each case. Also were made x-rays of hands and/or feet; in some cases of persistent doubt about RA diagnosis was done comparative MRI of hands. Percentages and averages were calculated for the demographic and clinical characteristics of the cohort of patients in which final diagnosis of OA was made. Results: From 2841 patients evaluated, in 1511 patients (53.2%) diagnosis of RA was confirmed, the remaining 1330 patients (46.8%) had a wrong diagnosis of RA. Between incorrect differential diagnosis were found: osteoarthritis in 896 patients (67.36%), systemic lupus erythematosus in 104 patients (7.81%), Sjögren syndrome in 50 patients (3.75%), spondyloarthropathies in 45 patients (3.38%), gout in 28 patients (2.1%) and other diagnoses in 15.56% of the remaining population. As above mentioned, 896 patients (67.36% of misdiagnosed patients) had finally OA. Of this patients, 629 (76.2%) were women and 267 (29.79%) men, with an average age of 59.5 years (range between 9-92 years). False positive diagnosis of RA was made on the basis of proximal or distal compromise in hands associated with low level positive rheumatoid factor; many of patients didn't have x-ray of hands, ultrasonography or MRI. Majority of these patients were followed not on a regular basis by general physicians or internists and treated with non-biologic and biologic (n=2) disease modifying anti-rheumatic drugs (DMARDs) in the past, for an average time of 4.5 years. Conclusions: Almost half patients with presumptive RA diagnosis in primary care centers in Colombia are misdiagnosed as shown in this large cohort. Most frequent diagnosis of patients misdiagnosed with RA was OA, being more than two thirds of them, predominantly women. This study shows the need for the implementation of specialized clinics in RA with early referral approaches and educational strategies for primary care physicians and other related specialists in order to avoid the clinical impact of this wrong diagnosis. Disclosure of Interest: None Declared